The effect of sulphate reducing bacteria on the hydrogen absorption of cathodically protected high strength low alloy steel - Kilgallon, P. J. (Cranfield University, 1994)
The hydrogen embrittlement of two HSLA steels was studied in conditions typical of the marine environment. Double cantilever beam specimens, heat treated to produce the microstructure in the heat affected zone of a weld, were tested in seawater containing sulphate reducing bacteria (SRB) over a range of cathodic protection (CP) potentials and the threshold stress intensities ([Threshold Stress Intensity]) were recorded. The hydrogen concentration absorbed by the steel ([Surface Hydrogen Concentration]) was measured and shown to be higher at more negative CP potentials and significantly increased when SRB were present. An inverse relationship was established between log [Threshold Stress Intensity] and ([Surface Hydrogen Concentration]. It was concluded that crack propagation occurs by a single mechanism whether or not SRB are present. Three point bend specimens of both steels were machined from welded plate. Corrosion fatigue tests were carried out in seawater with and without SRB. The presence of active SRB caused increased crack growth rates. Sediment samples were collected from the River Mersey and the base of a North Sea platform. In addition, SRB were added as an inoculum to artificial seawater. SRB numbers were enumerated and their activities assessed by measuring the concentrations of sulphide generated. Hydrogen permeation tests were performed on steel held at a range of CP potentials and exposed to each environment. Measurements were also carried out in seawater containing chemically prepared sulphides. Hydrogen absorption was shown to be enhanced when SRB were present and to be related to the total sulphide (TS) concentration in the environment. High hydrogen concentrations were produced by chemically prepared sulphides and the nature and thickness of the sulphide film appeared to be important in determining the extent of hydrogen absorption. Chemically produced sulphide gave sustained levels of absorbed hydrogen, but those generated biogenically decayed rapidly unless the TS concentration was maintained in the solution.